2016
DOI: 10.1007/s10555-016-9650-0
|View full text |Cite
|
Sign up to set email alerts
|

From transformation to metastasis: deconstructing the extracellular matrix in breast cancer

Abstract: The extracellular matrix (ECM) is a guiding force that regulates various developmental stages of the breast. In addition to providing structural support for the cells, it mediates epithelial-stromal communication and provides cues for cell survival, proliferation, and differentiation. Perturbations in ECM architecture profoundly influence breast tumor progression and metastasis. Understanding how a dysregulated ECM can facilitate malignant transformation is crucial to designing treatments to effectively target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 126 publications
(156 reference statements)
1
111
0
3
Order By: Relevance
“…HCC1937 cells were chosen because they showed a clear response in the earlier experiments and are derived from a primary tumour and so represent pre-metastatic cells [ 28 ]. This was of particular interest as modifications to the ECM at the primary site are widely regarded as essential for metastasis initiation [ 51 , 52 ]. ECM from HCC1937 was highly supportive of attachment and spreading of HCC1937 cells.…”
Section: Discussionmentioning
confidence: 99%
“…HCC1937 cells were chosen because they showed a clear response in the earlier experiments and are derived from a primary tumour and so represent pre-metastatic cells [ 28 ]. This was of particular interest as modifications to the ECM at the primary site are widely regarded as essential for metastasis initiation [ 51 , 52 ]. ECM from HCC1937 was highly supportive of attachment and spreading of HCC1937 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix stiffness in TMEs mechanistically is another mechanical cause for hypoxia-induced tumor metastasis [242]. Matrix stiffness can be made stiffer upon cross-linkages among collagen fibers by LOX, one of products secreted by tumor cells that are under hypoxic conditions [243][244][245].…”
Section: Hypoxia-induced Reexpression Of Fn In Tumor Cells and Cancermentioning
confidence: 99%
“…This occurs not only by providing optimal contractile forces for the migration of tumor cells, but also by affecting signaling (mechanotransduction), which can alter growth and even responses to drugs. Work from the Weaver laboratory and others has shown that in the breast cancer setting, increasing stiffness of the ECM can drive increased metastasis and resistance to chemotherapy through different processes as reviewed elsewhere (Kaushik, Pickup, & Weaver, ). Surprisingly, and in contrast to existing studies in other cancers, recent modeling experiments from our own laboratory suggest that this may be different in melanoma.…”
Section: The Stromal Microenvironment In Resistance To Mapk Blockadementioning
confidence: 99%